Effect of Different Doses of Fermented Organic Feed on the Growth Performance of Oithona sp. in Semi-Mass Culture Condition - Suminto Suminto; Diana Chilmawati; Dicky Harwanto (Fisheries and Marine Science Faculty - Jenderal Soedirman University, 2018)
This research was aimed to know the effect of different fermented organic feed on the growth performance of Oithona sp. in semi-mass culture condition. The Oithona sp. cultures were fed with mixed organic fermentation of pulp, bran and fish meal by using probiotic microbes and phytoplankton cells. There were 4 treatments and 4 replicates. Treatment A was the Oithona sp. cultured with added Chaetoceros calcitrans cells without fermented organic feed (0 g ∙ L–1 of medium culture). While B, C, and D were added with the same numbers of that C. calcitrans cells of 2x106 cells ∙ mL–1 and 0.5 g ∙ L–1, 1.0 g ∙ L–1, 1.5 g ∙ L–1 of fermented organic feed, respectively. The results showed that the dosage of fermented organic feed had significantly different effect (P < 0.05) on the growth performance of Oithona sp. culture. The best growth performance of Oithona sp. showed by adding 0.5 g ∙ L–1 of fermented organic feed, with total density of 7.09 ± 0.11 ind ∙ mL–1, population growth rate of 0.116 ± 0.002 ind ∙ d–1 and eggs production of 7.88 ± 0.93 eggs ∙ ind–1 of adult.